The association of shift work and metabolic syndrome among female nurses in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. - Ahmad Faris, Awang (2010)
Shift workers were found to be at risk for coronary heart disease (CHD). Lately many health organizations have clustered the risk factors for CHD and diabetes to a syndrome called metabolic syndrome. This study was designed to determine the prevalence of metabolic syndrome using the definition by NCEP (ATP III), to describe the characteristic of female nurses in HUSM, Kubang Kerian with metabolic syndrome and to determine the association between shift work and metabolic syndrome among female nurses in HUSM, Kubang Kerian, Kelantan. A cross sectional study was conducted between January to April 2009 among 404 female nurses in HUSM, Kubang Kerian. There were 227 shift workers and 177 day workers. All workers who fulfilled the study criteria were included in this study. Data questionnaire which consists of sociodemographic, occupational history and physical activity as well as DASS 42 questions (validated Malay version). Anthropometric, blood pressure measurement and fasting venous blood were taken from each subject for fasting lipid profile and fasting blood sugar. Data were analysed by ttest, chi-square test and multiple logistic regression. Majority of the respondents were Malay nurses with the mean age (SD) of 42.1 (7.19) years old. The mean (SD) duration of employment was 17.8 (6.33) years. Majority of nurses were physically inactive (91.1%) and 14.1% were having stress. The overall prevalence of metabolic syndrome was 24.3% (95% CI: 20.1, 28.5). The significant factors associated with metabolic syndrome after multivariables analyses were total duration of employment (years) and one way commuting time to work (minutes). High prevalence of metabolic syndrome indicates that nurses are occupational high risk group for CHD. Occupational factors significantly associated with metabolic syndrome in this study are total duration of employment and one way commuting time to work, however there is no significant relationship between metabolic syndrome with shift work and stress.